Development of Adjuvant-Free Bivalent Food Poisoning Vaccine by Augmenting the Antigenicity of Clostridium perfringens Enterotoxin - Suzuki, Hidehiko; Hosomi, Koji; Nasu, Ayaka; Kondoh, Masuo; Kunisawa, Jun (Frontiers in Immunology, 2018)
Clostridium perfringens enterotoxin (CPE) is a common cause of food poisoning and hyperkalemia-associated death. Previously, we reported that fusion of pneumococcal surface protein A (PspA) to C-terminal fragment of CPE (C-CPE) efficiently bound mucosal epithelium so that PspA-specific immune responses could be provoked. In this study, we found that fusion of C-CPE with PspA augmented the antigenicity of C-CPE itself. These findings allowed us to hypothesize that fusion of C-CPE and another food poisoning vaccine act as a bivalent food poisoning vaccine. Therefore, we constructed an adjuvant-free bivalent vaccine against CPE and cholera toxin (CT), which is a major food poisoning in developing country, by genetically fusing CT B subunit to C-CPE. Because of the low antigenicity of C-CPE, immunization of mice with C-CPE alone did not induce C-CPE-specific immune responses. However, immunization with our vaccine induced both C-CPE- and CT-specific neutralizing antibody. The underlying mechanism of the augmented antigenicity of C-CPE included the activation of T cells by CTB. Moreover, neutralizing antibodies lasted for at least 48 weeks and the quality of the antibody was dependent on the binding activity of CTB–C-CPE to its receptors. These findings suggest that our fusion protein is a potential platform for the development of an adjuvant-free bivalent vaccine against CPE and CT.